Prevalence of cardiovascular disorders among Iranian elite athletes - Salehi, S.; Shahpar, F. M.; Norouzi, G.; Ghazalian, F.; Esfehani, M. P.; Yekta, A. H. A. (Asian Journal of Sports Medicine, 2016)
Background: Athletes` health is an important issue and for promoting it, pre-participation examination (PPE) is widely performed by responsible bodies around the world..